Aplicação do modelo Black-Sholes e Binomial para precificação de opções europeias - SOARES, Rafael Ferreira Santos (2021)
In this work, we will study the pricing of a european type call option, show the factors that positively and negatively affect the price of an option and we will use the Black-Sholes and Binomial mathematical models for European type call option pricing. We also present an application of the models studied for pricing options for Petroleo Brasileiro SA - PETROBRAS.